Assessment of lower urinary tract symptoms in patients with Parkinson's disease. - Mejía-Rios, Laura C.; Hernández-Hidalgo, Juan de D.; Villaseñor-Álvarez, Karina; Ahedo-García, Karla M.; López-Valdez, Rodrigo A.; Manguilar-López, Ulises; Moreno-Palacios, Jorge (Boletín del Colegio Mexicano de Urología)
Objective: The objective of the study was to evaluate lower urinary tract symptoms (LUTS) in patients with Parkinson's disease (PD) using the International Prostate Symptom Score (IPSS) and Neurogenic Bladder Symptom Score (NBSS) questionnaires and assess their correlation between them. Materials and methods: An observational, cross-sectional, descriptive study was conducted, in patients over 18 years of age with a PD diagnosis were selected and evaluated to the urology service, where they were completed the IPSS and NBSS questionnaires. Results: Seventy-five patients with PD were evaluated. The NBSS questionnaire revealed a higher prevalence in the storage/emptying symptom domain. In the IPSS questionnaire, the most common symptoms were storage symptoms, especially urgency and nocturia, with a predominance of moderate symptom severity in both men and women. The NBSS questionnaire is consistent with the information obtained by the IPSS. No significant differences were observed when analyzing between sex or the time of evolution of the disease. Conclusion: LUTS are very common in patients with PD. Storage symptoms are the most frequently reported by patients. Symptoms occur in similar proportions between men and women, and these can occur from the onset of the disease, so early assessment by an urologist should be recommended in all these patients.